2018
DOI: 10.1364/ol.43.003196
|View full text |Cite
|
Sign up to set email alerts
|

10  W-level gain-switched all-fiber laser at 28  μm

Abstract: We report a simply designed gain-switched all-fiber laser emitting a maximum average output power of 11.2 W at 2.826 µm. The corresponding extracted pulse energy is 80 µJ at a pulse duration of 170 ns. These performances significantly surpass previous gain-switched demonstrations and are close to the state-of-the-art Q-switched laser performances near 2.8 µm, but with a much simpler and robust all-fiber design. The spliceless laser cavity is made of a heavily erbium-doped fluoride glass fiber and is bounded by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 31 publications
(35 reference statements)
1
19
0
Order By: Relevance
“…Paradis et al recently reported a gain-switched all-fiber laser emitting at 2.8 μm with an average output power in excess of 11 W. Two individual FBGs were again inscribed with the aid of a phase mask into the opposite ends of the fiber at a Bragg wavelength of 2.826 μm. Their spectral widths and reflectivities were 0.6 nm/90% for the high reflectivity FBG and 2.2 nm/5% for the low reflectivity (output-coupling) FBG [43]. It is important to note that in this work the gratings were inscribed directly through the protective coating, i.e., without removing the coating prior to inscription in order to preserve the integrity and the robustness of the pristine fiber.…”
Section: Phase Mask Techniquementioning
confidence: 99%
“…Paradis et al recently reported a gain-switched all-fiber laser emitting at 2.8 μm with an average output power in excess of 11 W. Two individual FBGs were again inscribed with the aid of a phase mask into the opposite ends of the fiber at a Bragg wavelength of 2.826 μm. Their spectral widths and reflectivities were 0.6 nm/90% for the high reflectivity FBG and 2.2 nm/5% for the low reflectivity (output-coupling) FBG [43]. It is important to note that in this work the gratings were inscribed directly through the protective coating, i.e., without removing the coating prior to inscription in order to preserve the integrity and the robustness of the pristine fiber.…”
Section: Phase Mask Techniquementioning
confidence: 99%
“…Recently, the 10 W-level gain-switched all-fiber Er 3+ :ZBLAN laser operating at 2.826 μm was reported. This laser was able to generate maximum average output power of 11.2 W with pulse energies up to 80 μJ and a pulse duration as short as 170 ns [21]. The longest wavelength achieved from gain switched Er 3+ :ZBLAN was 2.87 μm [23].…”
Section: Introductionmentioning
confidence: 99%
“…Gain-switched (GS) operation of a Dy 3+ :ZBLAN laser was predicted by numerical modeling in [19], but experimental results were not demonstrated, up to now. GS has proved a reliable, compact and relatively simple technique to generate nanosecond pulses at wavelengths around 3-3.55 μm [20][21][22][23][24][25]. In the GS regime the pulse operation is obtained by switching gain on/off by modulating the pump laser.…”
Section: Introductionmentioning
confidence: 99%
“…Using thulium-and holmium-doped fibres, a gain-switched laser operating at wavelengths up to 2.1 μm was realized [17]. On the other hand, using an erbium-doped fluoride fiber [18], pulses at 2.8 μm were generated.…”
Section: Introductionmentioning
confidence: 99%